Caldwell letters, - Caldwell, R. S.
Two letters from Captain R. S. Caldwell of the First Oregon Cavalry. The first is from Fort Vancouver, dated January 21, 1864 and the second is from Camp Watson, Oregon, dated September 20, 1864. He describes it being a "rather dull business" since the Indians are quiet. He also talks about the inadequate pay for troops. His second letter describes the need for troops in Oregon.